Monitoring drug variability in optimizing the treatment of psychiatric disorders - Jovanović, Marija (Archives of Pharmacy, 2022)
Psychiatric disorders significantly contribute to the overall burden of diseases in the world's population. Antipsychotic drug therapy is the main treatment for patients with schizophrenia or psychosis. These drugs show great variability in pharmacokinetic characteristics, and consequently in drug level and therapeutic response. Therefore, Therapeutic Drug Monitoring (TDM) is recommended for many drugs from this group (1). Sources of variability can be demographic characteristics, pathological or genetic factors. Moreover, pharmacokinetic, but also pharmacodynamic interactions may significantly contribute to the variability in drug response. Monitoring of clozapine antipsychotic therapy and potential interactions will be presented on the adult psychiatric patients. The analysis of potential drug-drug interactions was performed considering all administered drugs. In general, pharmacodynamic interactions may cause additive, synergistic, or antagonistic effects between drugs. In the study population, interactions related to enhanced adverse effect of clozapine have often been described. Regarding pharmacokinetic interactions, the most common are those related to the induction or inhibition of cytochrome P450 (CYP 450) metabolic isoenzymes. Hence, the effect of valproic acid on clozapine metabolism has been detected in several occasions. Further analysis of TDM data contributes to the understanding of the effect of this antiepileptic drug on clozapine levels. Monitoring drug variability is the basis for optimizing the treatment of psychiatric disorders. In collaboration with other health care professionals, pharmacists have a significant role in dosing optimization, especially in the prevention and management of drug-drug interactions.